الإمام أبو الوليد الباجي أديبا وشاعرا (ت 474 هـ) - بلاعدة, العمري (Université de M'sila, 2017)
مما هو معلوم أن الإمام أبا الوليد الباجي كان في بداية حياته ومشواره العلمي مهتما بالأدب والشعر كثيرا حتى أنه كان يجمع دواوين الشعر ويحفظها، وقد ساعده على ذلك الوسط العائلي الذي كان يعيش فيه، حيث كما ذكرنا سابقا أنه تلقى العلم في أوّل مراحله على خاله أبي شاكر الذي يعتبر من الخطباء البلغاء، ومن الشعراء الفصحاء المشهورين بالأندلس، فاستفاد منه كثيرا خاصة في هذا الجانب حتى صار بارعا في الأدب وممارسة الشعر. وقد بدأ أبو الوليد الباجي حياته كشاعر يمدح الأمراء والرؤساء والملوك، سواء أثناء إقامته بالأندلس أو بعد رحلته إلى المشرق، ومروره بمصر والقيروان، فكان أبو الوليد الباجي لا يمر ببلد في رحلته المشرقية إلا ويقول شعرا حتى احتاج في سفره إلى القصد بشعره. وقد تولى ابنه أبو القاسم أحمد جمع أشعاره، لكن لم يصل إلينا منه سوى ما أوردته تلك المصادر التي ترجمت للإمام الباجي. والظاهر أن جلّ أشعار أبي الوليد الباجي نظّمها بعد عودته من رحلته المشرقية، وبعد أن رسخت قدمه في العلم. وقد تضمن شعر أبي الوليد الباجي جملة من الأغراض المختلفة، والتي تعكس تجربته في الحياة، ولكن الغالب على موضوعاته الشعرية الرثاء والحمد والتأمل abstract It is well known that the Imam Abu Walid Baji was at the beginning of his life and his career Scientific interested in literature and poetry so much that he was collecting collections hair and protect it, has helped him so family environment in which he lived, where as we mentioned earlier that he had received the flag in the first stages of his uncle Abu Shakir, who is one of the preachers rhetoricians, and poets eloquent renowned Andalusia, benefiting from a private lot in this aspect until he became proficient in the literature and practice of poetry. Has begun Abu Walid Beji his life as a poet praised the princes and presidents and kings, both during his stay in Andalusia or after his trip to the Orient, and passage in Egypt and Kairouan, was Abu Walid Beji not pass country in his Eastern only say poetry until needed in traveling to the intent hair. He took his son Abu al-Qasim Ahmad collection of his poems, but it was not up to us it only those sources reported that translated to the Imam Beji. It seems that most of the poems of Abu Walid Beji organized after returning from his trip Eastern, and after that established by science. The hair included Abu Walid Beji a number of different purposes, and that reflect his experiences in life, but mostly on themes poetic lamentation and praise and meditation.
Keywords: إحكام الفصول في أحكام الأصول؛ مختصر المختصر في مسائل المدونة؛ تفسير القرآن الكريم؛ الأغراض الشعرية.